2002
DOI: 10.1002/1616-3028(200203)12:3<187::aid-adfm187>3.0.co;2-e
|View full text |Cite
|
Sign up to set email alerts
|

Determining Protein Size Using an Electrochemically Machined Pore Gradient in Silicon

Abstract: Porous silicon films displaying a distribution of pore dimensions can be generated by electrochemically etching silicon in aqueous ethanolic HF using an asymmetric electrode configuration. The median pore size and breadth of the size‐distribution in the film can be set by adjusting the HF concentration, current density, and position of the counter electrode relative to the silicon electrode. Films with pore sizes in the range of a few nanometers are used as size‐exclusion matrices to perform an on‐chip determi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
115
0
4

Year Published

2004
2004
2012
2012

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 118 publications
(123 citation statements)
references
References 16 publications
3
115
0
4
Order By: Relevance
“…A surface topography within the nanometer range may not exert sufficient physicochemical effects on wettability. The physical appearances of the laterally etched pSi surface that we obtained were found to be similar to those previously attained by Sailors group [25]. For all currents used in this work we were able to avoid electropolishing the surface.…”
Section: Lateral Anodisationmentioning
confidence: 48%
See 1 more Smart Citation
“…A surface topography within the nanometer range may not exert sufficient physicochemical effects on wettability. The physical appearances of the laterally etched pSi surface that we obtained were found to be similar to those previously attained by Sailors group [25]. For all currents used in this work we were able to avoid electropolishing the surface.…”
Section: Lateral Anodisationmentioning
confidence: 48%
“…The possibility to fabricate pSi surfaces containing a distribution of pore sizes by anodisation in an asymmetrical arrangement has been described previously [25]. The current within the electrolytic solution varies as a function of distance of the electrode to the counter electrode due to resistance of the electrolyte, thus leading to a decrease in current density as the distance from the electrode increases [25,26]. This dependence can be exploited to generate a surface displaying a gradient of pore features ranging from large (1-3 µm) to small (5 nm) on a single surface [27].…”
Section: Introductionmentioning
confidence: 46%
“…This confirms the current density chosen for the anodisation of the gradient is optimal and suggests that any further increase in current density will result in the collapse of the pore structure. Furthermore, the distribution in structural colour and visual characteristics were similar in comparison to previously published lateral gradients reported by Sailor et al 24 and Khung et al 4 .…”
Section: Preparation Of Porous Silicon Gradientsmentioning
confidence: 48%
“…The non-linear nature of the gradient could be attributed to the non-linear decrease in current density across the substrate. Previous studies have observed similar results 24,25 . Several HF/ethanol ratios were also investigated and it was found that increasing the concentration of HF led to a steeper decline in the pore size along the gradient.…”
Section: Preparation Of Porous Silicon Gradientsmentioning
confidence: 50%
“…En este sentido en el silicio poroso se han efectuado gran cantidad de estudios, existen publicaciones referentes a la calcificación [2][3][4][5][6][7][8][9][13][14][15][16][17], adhesión y cultivo de células [18][19][20][21], redes neuronales [22], adsorción de proteínas [23][24][25][26] y estudios de biodegradabilidad [27][28][29][30][31], así como de biocompatibilidad in Vivo [32,33]. Además se han hecho estudios sobre problemas que pueden plantearse a la hora de utilizarlo en seres humanos, como por ejemplo, la esterilización en autoclave [34] y otras técnicas de esterilizado [35], o sobre técnicas de fabricación con el objeto de que no sea perjudicial para la salud [36].…”
Section: Definicionesunclassified